Description of the Application of Spiritual Emotional Freedom Technique (SEFT) on Anxiety in Adolescents Who Do Early Marriage - Samsugito, Iwan; Nur, Syukma Rhamadani Faizal; Sari, Catur Permata (Fakultas Kedokteran, 2023)
Background: According to Law No. 16 of 2019, the maximum age for marriage is 19 years to prepare for physical and psychological maturity so that married couples are expected to be happy. However, early marriage couples still occur, which can cause conflicts in the household and make the wife or husband experience anxiety. Anxiety, in principle, is the body's response to a threat and serves as a warning against threatening situations. Objective: To determine the application of SEFT to reducing the anxiety of adolescents who engage in early marriage Method: This study uses a case study. Results: Before the SEFT, the anxiety level was measured using the Hamilton Anxiety Rating Scale (HARS) Questionnaire. It was found that four respondents experienced moderate anxiety and one experienced severe anxiety, and after three treatments, there was a decrease in anxiety levels; three experienced mild anxiety, and two experienced moderate anxiety. Conclusion: SEFT can reduce the anxiety of adolescents who marry early